Influencia del marketing en el nivel de participación de mercado de las mypes del sector vidrierías del distrito de Trujillo - 2012. - Reyes Paredes, Jenny Mabel (2012)
The present work is to research problem how the influence of marketing contributes to the level of market share of sector mypes glassworks district Trujillo? Taking as a hypothesis, the influence of marketing contributes positively to the level of market share of the sector mypes glassworks district of Trujillo. For which was taken as the total population of the district of Trujillo glassworks, Being a study population of moderate size, we worked with the entire study population, with the 64 glassworks in the district of Trujillo. (Sample Census. The research design selected is no experimental cross. The reason for this choice is because there is no way to influence the context. For purposes of this study addressed the two types of data (secondary and primary). Were taken as sources of secondary information research industry. Primary information was obtained through the use of surveys, which are designed with open and closed questions. It was concluded that the environment is favorable to the glassworks, the purchasing power people has increased and the construction sector is in constant growth. It was shown that the use of marketing contributes positively to the level of market share of industry in the district of Trujillo